Kompetensi Kepala Madrasah dalam Manajemen Pembiayaan Pendidikan - Maghfuri, Safiul; Jalaluddin, Jalaluddin; Ramlah, Ramlah; Miftahuddin, Miftahuddin (Journal of Educational Research, 2023)
This article reveals the managerial competence of the Head of Madrasah, especially in terms of education financing at the Anwarul Falah Tsanawiyah Madrasah, Pebenaan Village, Keritang Indragiri Hilir District, Riau. This article comes from qualitative research using data collection through observation, interviews and documentation. The research results show that the Head of Madrasah has carried out good managerial processes in curriculum management. At the planning stage, the Madrasah Head combines an administrative approach with a grass roots approach which is prepared based on student needs. Stages of managerial implementation of the curriculum, the Head of the Madrasah divides the stages into two levels, namely the implementation of the madrasah and class level curriculum, meanwhile for the supervisory stage the Head of the Madrasah applies formative and summative evaluations. The managerial ability of the Head of Madrasah in managing personnel management is said to be quite good, but there are several things that are still lacking, namely at the planning and evaluation stages. Artikel ini mengungkap kompetensi manajerial Kepala Madrasah khususnya dalam hal pembiayaan pendidikan di Madrasah Tsanawiyah Anwarul Falah Desa Pebenaan Kecamatan Keritang Indragiri Hilir Riau. Artikel ini berasal dari sebuah penelitian kualitatif dengan pengumpulan data secara observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa Kepala Madrasah sudah melakukan proses manajerial dengan baik pada manajemen kurikulum. Pada tahapan perencanaan Kepala Madrasah memadukan antara administrative approach dengan grass roots approach yang disusun berdasarkan atas kebutuhan siswa. Tahapan pelaksanaan manajerial kurikulum, Kepala Madrasah membagi tahapan menjadi dua tingkatan yaitu pelaksanaan kurikulum tingkat madrasah dan kelas, sementara itu untuk tahapan pengawasan Kepala Madrasah menerapkan evaluasi formatif dan sumatif. Kemampuan manajerial Kepala Madrasah dalam mengelola manajemen personil dikatakan cukup baik, namun terdapat beberapa hal yang masih kurang yaitu pada tahapan perencanaan dan evaluasi.